Diagnostic accuracy of portable instrumental devices to measure sleep bruxism: a systematic literature review of polysomnographic studies. (8th July 2014) - Manfredini, D.; Ahlberg, J.; Castroflorio, T.; Poggio, C. E.; Guarda‐Nardini, L.; Lobbezoo, F.
Summary This study systematically reviews the sleep bruxism (SB) literature published in the MEDLINE and Scopus databases to answer the following question: What is the validity of the different portable instrumental devices that have been proposed to measure SB if compared with polysomnographic (PSG) recordings assumed as the gold standard? Four clinical studies on humans, assessing the diagnostic accuracy of portable instrumental approaches (i.e. Bitestrip, electromyography (EMG)‐telemetry recordings and Bruxoff) with respect to PSG, were included in the review. Methodological shortcomings were identified by QUADAS‐2 quality assessment. Findings showed contrasting results and supported only in part the validity of the described diagnostic devices with respect to PSG. The positive predictive value (PPV) of the Bitestrip device was 59–100%, with a sensitivity of 71–84·2%, whilst EMG‐telemetry recordings had an unacceptable rate of false‐positive findings (76·9%), counterbalanced by an almost perfect sensitivity (98·8%). The Bruxoff device had the highest accuracy values, showing an excellent agreement with PSG for both manual (area under ROC = 0·98) and automatic scoring (0·96) options as well as for the simultaneous recording of events with respect to PSG (0·89–0·91). It can be concluded that the available information on the validity of portable instrumental diagnostic approaches with respect to PSG recordings is still scarce and not solid enough to support any non‐PSG technique's employ as a stand‐alone diagnostic method in the research setting, with the possible exception of the Bruxoff device that needs to be further confirmed with future investigations.